Histological comparative analysis of Bowman layer grafts procured using 3 different techniques - Son, Hyeck Soo; Moon, Loren; Wang, Jiangxia; Eberhart, Charles G.; Jun, Albert S.; Srikumaran, Divya; Soiberman, Uri S. (Cornea, 2023)
Purpose: - The objective of this study is to perform a histological analysis of Bowman layer (BL) grafts. - Methods: - BL grafts were procured from 13 human cadaver corneal tissues using 3 different donor preparation techniques. Subsequently, the grafts were fixed in 10% buffered formalin phosphate and embedded in paraffin. Hematoxylin and eosin sections of BL grafts were obtained and analyzed under a light microscope. BL and full graft thickness were measured using an image-processing software. - Results: - All 13 BL grafts contained residual anterior stromal tissue. BL stripping using Kelman-McPherson and Moorfield forceps (technique 3) achieved the thinnest graft thickness with a mean full graft thickness of 18.7 μm (95% confidence interval [CI], −9.8 to 47.2) at the thinnest point of the graft, whereas BL procurement using the Melles lamellar dissector (technique 2) led to the highest mean full graft thickness of 279.9 μm (95% CI, 251.4-308.5) even at the thinnest area of the graft. By contrast, BL dissection using a blunt dissector (technique 1) provided a mean full graft thickness of 70.2 μm (95% CI, 40.4-100.1) at the graft's thinnest point. Although peripheral graft tears occurred in 50%, 50%, and 100% of techniques 1, 2, and 3, respectively, intact 6.25-mm diameter BL grafts could be secured in 50%, 100%, and 80% of techniques 1, 2, and 3, respectively. - Conclusions: - None of the techniques used led to the procurement of pure BL grafts devoid of the anterior stroma. Peripheral scoring with a thin needle and tissue manipulation with Kelman-McPherson and Moorfield forceps led to the thinnest grafts in this study.
Gesehen am 24.07.2023